Aplikasi Augmented Reality Game Edukasi Untuk Pengenalan Organ Tubuh Manusia - Wibowo, Pungky Ary, Endah Sudarmilah, S.T., M.Eng (2015)
Human organs is a vital instrument in the human body. In practice, the introduction of human organs in primary school in need of a 3-dimensional props are only owned by the school. While primary school children to be interested in new things. Therefore it takes innovation to bridge both these problems with the application of augmented reality educational game to interest and assist students in human organs. The researchers design and build augmented reality applications educational game with a method of SDLC (System Development Life Cycle). Applications built using Unity3D, Blender as modeling, vuforia Augmented Reality SDK to form, and programming with playmaker. Application of augmented reality games have games that matter taken from the material introduction of human organs. Tested research results to students SDIT Muhammadiyah Al-Kautsar Kartasura IV Class C with students demonstrating and operate directly. Based on the data from the questionnaires, applications created can attract and help students learn in human organs.